Performance measurement framework for product–service systems development: a balanced scorecard approach. (9th December 2013) - Chirumalla, Koteshwar; Bertoni, Alessandro; Parida, Aditya; Johansson, Christian; Bertoni, Marco
The paper proposes a framework for analysing the performances of product–service systems (PSSs) development processes using a balanced scorecard (BSC) as an instrument to guide the implementation and the evaluation of new methods and tools. Emerging from a case study in the aerospace industry, the paper discusses the main challenges in PSS development and proposes a performance measurement framework for PSS development based on multi–criteria indicators. Finally, the benefits of a framework for PSS development performance measurement are discussed.